Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw dipadu Talking Stick untuk Meningkatkan Keaktifan Belajar Siswa SMK Batik 1 Surakarta pada Mata Pelajaran Ekonomi Bisnis Tahun Pelajaran 2018/2019 - Agnes Indah Pratiwi; Soetarno Joyoatmojo; Jonet Ariyanto Nugroho (Department of Economics Education, Universitas Sebelas Maret, 2023)
The purpose of this study was to improve the student learning activeness of SMK Batik 1 Surakarta on Business Economics subjects through the Jigsaw cooperative learning model combined with Talking Stick. This study is a Classroom Action Research (CAR) conducted in 2 cycles. Each cycle consists of 4 stages, namely: (1) Action planning; (2) Implementation of Actions; (3) Observation or Observation; and (4) Reflection. The subjects of this study were students of class X OTKP 1 of SMK Batik 1 Surakarta with a total of 42 students. Data collection techniques are carried out through activities: (a) interviews; (b) observation; and (c) documentation. Data validity with source triangulation and method triangulation. Data analysis techniques with qualitative and quantitative data analysis. The results showed that through the application of the Jigsaw type cooperative learning model combined with the Talking Stick can increase student activity from pre-cycle to cycle I and from cycle I to cycle II. This is evident in the pre cycle, the percentage of student activity is 28.57%. The percentage of student learning activeness increased to 73.80% in the first cycle after the Jigsaw type cooperative learning model was applied combined with Talking Stick. The percentage of student learning activeness returns increased in the second cycle to 92.86%. The conclusion of class action research by applying the Jigsaw type cooperative learning model combined with the Talking Stick can increase the learning activeness of class X OTKP 1 students of SMK Batik 1 Surakarta on The Business Economic subjects in The school year 2018/2019.